2009
DOI: 10.4161/cc.8.12.8740
|View full text |Cite
|
Sign up to set email alerts
|

Whi3 regulates morphogenesis in budding yeast by enhancing Cdk functions in apical growth

Abstract: The Whi3 protein is associated with the endoplasmic reticulum, interacts with Cdc28, the budding-yeast Cdk, binds the mRNA of cyclin CLN3 and prevents accumulation of the Cdc28-Cln3 in the nucleus until late G 1 . Besides its function as a cell size regulator, Whi3 is strictly required for filamentous growth. Here we show that emerging buds in Whi3-deficient cells are considerably rounder than in wild-type cells, indicating that Whi3 is required to maintain apical growth during S phase. This defect was not sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…For the majority of pathogenic fungi, this transformation is an essential step in their infectious process, and modifications in plasma membrane and cell wall constituents have been implicated [40,41]. The mechanisms that trigger the transition to filamentous growth in S. cerevisiae are associated with carbon or nitrogen stresses [39,42]. The interplay between the filamentation process and protein quality control may be an important feature that deserves to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…For the majority of pathogenic fungi, this transformation is an essential step in their infectious process, and modifications in plasma membrane and cell wall constituents have been implicated [40,41]. The mechanisms that trigger the transition to filamentous growth in S. cerevisiae are associated with carbon or nitrogen stresses [39,42]. The interplay between the filamentation process and protein quality control may be an important feature that deserves to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The MAPK pathway regulates the expression of the cyclin CLN1, which encodes a G 1 cyclin . The different G 1 cyclins have different effects on the filamentation response (Loeb et al 1999;Colomina et al 2009). Elements of the morphogenetic checkpoint (Lew and Reed 1995) including the protein kinase Swe1 (Sia et al 1998;La Valle and Wittenberg 2001) are also important for filamentous growth regulation.…”
Section: Filamentous Growth Regulationmentioning
confidence: 99%
“…WHI3 is further involved in several developmental events, including mating and adhesive growth of haploid strains as well as filament formation and meiosis of diploids (Mö sch and Fink 1997; Gari et al 2001). Global studies have identified a large number of mRNAs that are bound by the Whi3 RRM domain (Colomina et al 2008(Colomina et al , 2009. A significant fraction of these Whi3 targets encode membrane and exocytic proteins involved in transport and cell wall biogenesis, indicating that Whi3 might be a general modulator of protein fate that affects cell integrity and organization of the actin cytoskeleton.…”
mentioning
confidence: 99%